Climate Finance Mapping in Mali and Senegal - Teno, Gabriel (International Livestock Research Institute, 2023)
The objective of this study is to review promised climate change financing allocated and available for the livestock sector and compare financing for adaptation to that for mitigation for Mali and Senegal. This includes a desk review of proposed or existing projects and examines the allocation of resources for climate adaptation and mitigation in livestock production systems or to support livestock-related livelihoods.